CORRELATION BETWEEN WATER QUALITY PARAMETERS AND VIBRIO SP. BACTERIA CONTENT IN TRADITIONAL VANNAMEI SHRIMP (LITHOPENAEUS VANNAMEI) CULTURE - Asni, Asni; Rahim, Rahim; Saleh, Ramlah; Landu, Anti; Muliadi, Muliadi (ITScience (Information Technology and Science), 2023)
Vannamei shrimp is a species of shrimp that is frequently cultivated using conventional methods. This is because vannamei crustaceans have favorable prospects and profits. Traditional Vannamei shrimp cultivation has great development potential, but preventing parasites and diseases that originate in the pond water when cultivating shrimp is impossible. The incidence of disease is closely correlated with parameters of water quality. Pathogenic microorganisms, specifically the Vibrio sp. bacteria, are responsible for one of the prevalent maladies affecting vannamei shrimp farms. Vibrio sp. bacteria produces vibriosis, the clinical symptoms of brownish-red gills, a crimson uropod and abdominal telson, and a sluggish swimming speed. This study aimed to determine the correlation between Vibrio sp. bacteria content and water quality parameters in conventional vannamei shrimp (Lithopenaeus vannamei) cultivation. This study employed exploratory methods and purposive sampling for its sampling. Isolation of microbes using selective media containing TCBSA. The colony abundance of Vibrio sp. bacteria was calculated using the Total Plate Count method. The results showed no significant correlation between the quality of pond water and the abundance of Vibrio sp. bacteria colonies in the traditional system of vannamei shrimp (Lithopenaeus vannamei) cultivation, with a correlation value of > 0.05.